Studi Pendahuluan Pengendapan Cerium, Lanthanum, dan Neodymium dari Larutan Klorida Menggunakan Sodium Karbonat pada Pengolahan Monasit Bangka - Trinopiawan, Kurnia; Avifa, Venny Nur; Susilo, Yarianto Sugeng Budi; Rakhma, Ersina; Supriyatna, Yayat Iman; Susanto, Iwan; Permana, Sulaksana; Soedarsono, Johny Wahyuadi (EKSPLORIUM, 2020)
Monazite mineral as associated mineral of tin mining in Bangka Belitung Islands contains light rare earth elements like Cerium (Ce), Lanthanum (La), and Neodymium (Nd). The objective of this study is to obtain the concentrates of rare earth carbonate through the precipitation process with sodium carbonate (Na2CO3) and determine the effect of concentration and volume of Na2CO3 on the precipitation recovery of Ce, La, and Nd. The preparation of the feed solution was carried out by following the monazite processing route using the alkali method includes the stages of decomposition, dissolution, and precipitation of radioactive elements. The highest precipitation recovery for Ce, La, and Nd are 10.84%, 7.81%, and 2.68% respectively in the use of Na2CO3 with a concentration of 30% wt and a volume of 55 mL.